TOWARD AN UNDERSTANDING OF NURSING KNOWLEDGE DEVELOPMENT - Le Thi Thanh Tuyen (Belitung Raya Foundation, Indonesia, 2018)
As nurses, we seek to better understand how to apply nursing knowledge in our daily practice. Nowadays, the term philosophy is widening used in many areas, including nursing. However, there is existence of unclear understanding about nursing knowledge development derived from standpoint of philosophical and methodological perspectives. This article discusses about this issue and mainly focus on empiricism, post positivistic view, the philosophy of Buddhism and an example related to asthma.